2013
DOI: 10.1002/jgrd.50553
|View full text |Cite
|
Sign up to set email alerts
|

Near‐surface air temperature lapse rates in the mainland China during 1962–2011

Abstract: [1] Land surface hydrological modeling is sensitive to near-surface air temperature, which is especially true for the cryosphere. The lapse rate of near-surface air temperature is a critical parameter when interpolating air temperature from station data to gridded cells. To obtain spatially distributed, fine-resolution near-surface (2 m) air temperature in the mainland China, monthly air temperature from 553 Chinese national meteorological stations (with continuous data from 1962 to 2011) are divided into 24 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
121
4
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(141 citation statements)
references
References 52 publications
15
121
4
1
Order By: Relevance
“…In addition to finding differences between standard and observed lapse rate, previous studies have found large subannual variations of Tlr (Chen et al, 2014;Kirchner et al, 2013;X. Li et al, 2013;Y.…”
Section: Annual Monthly and Seasonal Lapse Ratementioning
confidence: 88%
“…In addition to finding differences between standard and observed lapse rate, previous studies have found large subannual variations of Tlr (Chen et al, 2014;Kirchner et al, 2013;X. Li et al, 2013;Y.…”
Section: Annual Monthly and Seasonal Lapse Ratementioning
confidence: 88%
“…Nonetheless, this assumption has been proven to be erroneous numerous times (Minder et al, 2010;Rolland, 2003;Steenburgh et al, 1997). For instance, several studies have found large annual, seasonal, and diurnal variation of Tlr (Kirchner et al, 2013;Li et al, 2013;Chen et al, 2014;Li et al, 2015). Other studies have reported substantial differences in Tlr for each slope of the same mountain (Minder et al, 2010;Tang and Fang, 2006), which indicates the importance of microclimate for lapse rate.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, LRs are shallower in humid conditions than in dry ones (Blandford et al, 2008;Minder et al, 2010), but this is not always true (e.g., region 3). This is because humid air has a higher probability of being heated by latent heat released from condensation at higher elevations (Li et al, 2013). Latent heat release depends on atmospheric moisture content (Marshall et al, 2007).…”
Section: Spatial Distribution Of Lrs Derived From Nighttime Modis Tmentioning
confidence: 99%
“…In fact, these processes are sensitive to air temperature, especially in the cryospheric regions where it influences the melting of snow, glaciers, and permafrost. Additionally, exchanges of energy and water fluxes between the earth surface and atmosphere can be affected by air temperature (Li et al, 2013). However, due to the irregular and sparse distribution of observation stations, the continuous and accurate distribution of near-surface air temperature data across large areas is not…”
Section: Introductionmentioning
confidence: 99%